1994
DOI: 10.1038/jcbfm.1994.99
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Topography of Parkinsonism

Abstract: Summary: We used [ lB F]fluorodeoxyglucose/positron emission tomography e B F-FDG/PET) and a statistical model of regional covariation to study brain topographic organization in parkinsonism. We studied 22 patients with Parkinson's disease (PD), 20 age-matched normal volun teers, and 10 age-and severity-matched patients with pre sumed striatonigral degeneration (SND). We used FDGI PET to calculate global, regional, and normalized meta bolic rates for glucose (GMR, rCMR g lc, rCMR g lc/GMR). Metabolic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

32
287
2
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(326 citation statements)
references
References 58 publications
(23 reference statements)
32
287
2
5
Order By: Relevance
“…We have found that this disease is associated with a specific spatial covariance pattern involving metabolic abnormalities in basal ganglia thalamocortical functional/anatomic pathways (Eidelberg et al, 1994(Eidelberg et al, , 1997. Indeed, this PD-related covariance pattern (PDRP) has been detected in multiple independent patient populations scanned in the resting condition (Moeller et al, 1999;Feigin et al, 2002;Lozza et al, 2004;Asanuma et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…We have found that this disease is associated with a specific spatial covariance pattern involving metabolic abnormalities in basal ganglia thalamocortical functional/anatomic pathways (Eidelberg et al, 1994(Eidelberg et al, , 1997. Indeed, this PD-related covariance pattern (PDRP) has been detected in multiple independent patient populations scanned in the resting condition (Moeller et al, 1999;Feigin et al, 2002;Lozza et al, 2004;Asanuma et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Studies combining neuroimaging and CSF in PD are scarce, but CSF A β correlate with reduced gray matter volume and associated neuropsychological function 22, 23. FDG‐PET studies have identified a widespread, specific pattern of reduced glucose metabolism in PD,24 most prominent in the frontoparietal and occipital cortices, even in the early stages of the disease 25. Cerebral glucose metabolism reflects cortical activation and synaptic density 26.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, network analyses of regional PET data have consistently revealed the presence of a reproducible abnormal spatial covariance pattern associated with parkinsonism (Eidelberg et al, 1994;Moeller et al, 1999;Lozza et al, 2004;Asanuma et al, 2005a). This PD-related pattern (PDRP) is characterized by pallido-thalamic and pontine hypermetabolism associated with relative metabolic decrements in premotor, prefrontal, and posterior parietal cortical regions (Carbon and Eidelberg, 2002;Asanuma et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…This PD-related pattern (PDRP) is characterized by pallido-thalamic and pontine hypermetabolism associated with relative metabolic decrements in premotor, prefrontal, and posterior parietal cortical regions (Carbon and Eidelberg, 2002;Asanuma et al, 2005a). We have attributed this abnormal metabolic topography to overactivity of internal pallidal (GPi) afferents from STN and consequent increases in inhibitory pallidal outflow to the ventral thalamus and pons (Eidelberg et al, 1994(Eidelberg et al, , 1997. To test this hypothesis, we quantified PDRP expression in patients with advanced disease undergoing stereotaxic subthalamotomy (Su et al, 2001).…”
Section: Introductionmentioning
confidence: 99%